CSF Findings in Chinese Patients with NMDAR, LGI1 and GABABR Antibody-Associated Encephalitis - Qiao S; Li H; Cui C; Zhang C; Wang A; Jiang W; Zhang S (Dove Medical Press, 2024)
Shan Qiao,1,2,* Haiyun Li,3,* Caisan Cui,4 Chong Zhang,1 Aihua Wang,1 Wenjing Jiang,3 Shanchao Zhang1,5 1Department of Neurology, the First Affiliated Hospital of Shandong First Medical University & Shandong Provincial Qianfoshan Hospital, Shandong First Medical University, Jinan, People's Republic of China; 2Department of Medical Genetics, School of Basic Medical Sciences, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China; 3Department of Geriatric Medicine, Qilu Hospital, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China; 4Department of Neurology, Qilu Hospital, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China; 5School of Medicine, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China*These authors contributed equally to this workCorrespondence: Shanchao Zhang, Email zhangshanchao2012@163.com; Wenjing Jiang, Email jiangwenjing@qiluhospital.comPurpose: CSF inflammation in subtypes of antibody-defined autoimmune encephalitis (AE) ranges in intensity from moderate to severe. In a retrospective, cross-sectional study, we characterized CSF findings in Chinese patients with anti-N-methyl-D-aspartate receptor encephalitis (NMDAR-E), anti-leucine-rich glioma-inactivated 1 encephalitis (LGI1-E), and anti-gamma aminobutyric acid-B receptor encephalitis (GABABR-E).Patients and Methods: The AE cases, including 102 NMDAR-E, 68 LGI1-E and 15 GABABR-E, were included. CSF inflammatory parameters consisted primarily of CSF leukocytes, oligoclonal bands (OCBs), and CSF/serum albumin ratios (QAlb). Ten serum cytokines were evaluated in order to classify AE subtypes.Results: 88% of NMDAR-E, 80% of GABABR-E, and 51% of LGI1-E patients had aberrant CSF features. In NMDAR-E, the CSF leukocyte count, CSF protein concentration, and age-adjusted QAlb were significantly higher than in LGI1-E, but did not differ from GABABR-E. Blood-CSF barrier dysfunction was less common in NMDAR-E patients with > 40 years old. On admission, inflammatory CSF response was more prevalent in NMDAR-E patients with a higher CASE score. With age < 60 years, CSF inflammatory changes were less frequent in LGI1-E patients, but more common in GABABR-E patients. MCP-1, IL-10, IL-1β, and IL-4 were potential classifiers for NMDAR-E, LGI1-E, and GABABR-E, and correlated substantially with CSF leukocyte count and QAlb.Conclusion: Subtype-specific patterns are formed by the various inflammatory CSF parameters in NMDAR-E, LGI1-E, and GABABR-E, and their correlation with disease severity, age, and disease duration. CSF inflammatory characteristics associated with MCP-1, IL-10, IL-1β, and IL-4 may be potential immunopathogeneses targeting markers for these AE subtypes.Keywords: autoimmune encephalitis, cytokines, neuroinflammation, cerebrospinal fluid